Egg Production, Blood Profile, and Histopathology in Japanese Quail with Phytogenic Additives - Murwani, R.; Anggraeni, R.; Muslih, M. H.; Yogantara, A. O.; Mulyono (Faculty of Animal Science, IPB University, 2024)
This study aimed to determine the effect of combining phytogenic Curcuma aeruginosa Roxb powder with C. xanthorizza standardized extract or with Anredera cordifolia leaf powder in an antibiotic-free diet on the egg production, red and white blood cell profile, fecal endoparasite, serum biochemistry, and intestinal and liver histopathology of Japanese quails. Four hundred eight-month-old Japanese quails were raised in 5-tier cages, randomly allocated into four treatments, namely: T0 (standard diet), T1 (standard diet plus 1% C. aeruginosa Roxb rhizome powder), T2 (standard diet plus 1% C. aeruginosa Roxb rhizome powder and C. aeruginosa extract (equal to 200 ppm standardized curcumin), and T3 (standard diet plus 1% C. aeruginosa Roxb powder and 1% A. cordifolia leaf powder). The data were analyzed using variance analysis (ANOVA). Duncan’s test was carried out at a 5% significant level when a significant effect was found. The results showed that weekly egg production was not affected by phytogenic addition, but egg production significantly increased on the last day of treatment (p<0.05). Combining 1% C. aeruginosa Roxb and 1% A. cordifolia significantly increased (p<0.05) erythrocytes, hemoglobin, hematocrit, leukocytes, lymphocytes, serum glucose, uric acid, creatinine, and AST. However, their values remained within the normal range of Japanese quails. No endoparasites were found in the fecal samples. The addition of phytogenic did not affect the height of intestinal villi and crypt depth (p>0.05). Interestingly, intestinal inflammation levels were reduced significantly in T1 and T2 compared to the control, while T3 was the same as the control (p<0.05). An elevated liver score was found (1 score higher) in T2 (p<0.05). This study suggests that phytogenic additives can help reduce normal intestinal inflammation (due to harsh intestinal environment) and improve the performance of laying Japanese quail, especially in the absence of endoparasites or infection.